Reliability and sensitivity of the notio device and aer-oscale service to quantify cyclists' drag coefficients in outdoor conditions - Bruez, A.; Caillou, Q.; Dugenne, T.; Peron, T.; Perrey, S.; Lambolais, T. (Journal of Science and Cycling, 2023)
Notio is a device based on a wind sensor which offers estimates of the CdA (drag coefficient multiplied by the area) of the pair cyclist and bike. Notio is used with specific analysis software, which computes CdA estimates after a ride. The Aeroscale Company proposes a half-day service with their own wind sensor and experimental protocol, to also deliver estimates of the CdA. In both cases, the main objective of a wind sensor is to give estimates in outdoor conditions. The Aeroscale specificity is that all experiments are done without any power sensor, in freewheel. In our study, we experimented Notio device and software as well as Aeroscale Service through an incremental protocol with increasing disks, which led us to obtain sensitivity measures of 4.5% for Notio and 0.5% for Aeroscale, with a reliability of 8% for Notio and 1% for Aeroscale.